Collaboration Between Nagari Government and The Migrant Community in the Development of Nagari Sulit Air, Kabupaten Solok - Heriza, Nadya; Hasbullah malau (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This study aims to describe the inhibiting factors in the collaboration between the Nagari government and the migrant community in the development of Nagari Sulit Air, Solok Regency. The objective is to identify the obstacles hindering this collaboration. The research adopts a qualitative approach with a descriptive method. Informants were selected using a purposive sampling technique, and data were collected through interviews with informants and direct observations in Nagari Sulit Air. The data are supported by documentation and other records available at the Nagari Sulit Air office. The data analysis process involved data reduction, data presentation, conclusion drawing, and verification. The study concludes that the factors impeding the collaboration include difficulties in land acquisition, economic conditions of the migrant community, the absence of a collaborative branding strategy, and differing opinions among stakeholders. Keywords: Collaboration, Nagari government, Migrant community, Nagari developmen